Analytical model of shear behaviour of a fully grouted cable bolt subjected to shearing. (December 2015) - Li, Xuwei; Nemcik, Jan; Mirzaghorbanali, Ali; Aziz, Naj; Rasekh, Haleh
Abstract: A fully grouted cable bolt is normally loaded at rock joints by a combination of the axial and shear forces causing both axial extension and shear deformation of the cable. The proposed analyses presented here attempts to predict the joint shear strength and shear displacement. The analyses are based on the statically indeterminate beam theory and some basic findings and conclusions of other researchers. Parametrical investigation is performed on four influence factors including bolt pretension, joint friction angle, concrete strength and bolt installation angle. Although the true plastic moduli of the cable bolt deflecting section at failure are the essential parameters in this analysis, they are practically impossible to determine. Thus, the average cable moduli obtained from the cable tensile strength tests were used. The proposed analytical model was compared with the experimental results, showing a good agreement. This analytical work aims to develop a simple tool for the practicing geotechnical engineer to effectively evaluate the cable shear behaviour and the influence of fully grouted cable bolts on joint shear resistance. Highlights: An analytical model is proposed about the shear behaviour of cable–reinforced joint. The shear strength of cabled joint and cable deformation are derived. Four influence factors are investigated parametrically. The model is experimentally validated.